Photothermal heating of titanium nitride nanomaterials for fast and uniform laser warming of cryopreserved biomaterials - Alvarez, Crysthal; Berrospe-Rodriguez, Carla; Wu, Chaolumen; Pasek-Allen, Jacqueline; Khosla, Kanav; Bischof, John; Mangolini, Lorenzo; Aguilar, Guillermo (Frontiers in Bioengineering and Biotechnology, 2022)
Titanium nitride (TiN) is presented as an alternative plasmonic nanomaterial to the commonly used gold (Au) for its potential use in laser rewarming of cryopreserved biomaterials. The rewarming of vitrified, glass like state, cryopreserved biomaterials is a delicate process as potential ice formation leads to mechanical stress and cracking on a macroscale, and damage to cell walls and DNA on a microscale, ultimately leading to the destruction of the biomaterial. The use of plasmonic nanomaterials dispersed in cryoprotective agent solutions to rapidly convert optical radiation into heat, generally supplied by a focused laser beam, proposes a novel approach to overcome this difficulty. This study focuses on the performance of TiN nanoparticles (NPs), since they present high thermal stability and are inexpensive compared to Au. To uniformly warm up the nanomaterial solutions, a beam splitting laser system was developed to heat samples from multiple sides with equal beam energy distribution. In addition, uniform laser warming requires equal distribution of absorption and scattering properties in the nanomaterials. Preliminary results demonstrated higher absorption but less scattering in TiN NPs than Au nanorods (GNRs). This led to the development of TiN clusters, synthetized by nanoparticle agglomeration, to increase the scattering cross-section of the material. Overall, this study analyzed the heating rate, thermal efficiency, and heating uniformity of TiN NPs and clusters in comparison to GNRs at different solution concentrations. TiN NPs and clusters demonstrated higher heating rates and solution temperatures, while only clusters led to a significantly improved uniformity in heating. These results highlight a promising alternative plasmonic nanomaterial to rewarm cryopreserved biological systems in the future.